2022
DOI: 10.3389/fimmu.2022.988536
|View full text |Cite
|
Sign up to set email alerts
|

The role of B cells in COVID-19 infection and vaccination

Abstract: B cells secrete antibodies and mediate the humoral immune response, making them extremely important in protective immunity against SARS-CoV-2, which caused the coronavirus disease 2019 (COVID-19) pandemic. In this review, we summarize the positive function and pathological response of B cells in SARS-CoV-2 infection and re-infection. Then, we structure the immunity responses that B cells mediated in peripheral tissues. Furthermore, we discuss the role of B cells during vaccination including the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 174 publications
0
38
0
1
Order By: Relevance
“…Initially, in the lymph node, naive B cells can interact with either macrophages or dendritic cells that carry SARS-CoV-2 antigens (N and S proteins) on their surface (20; 21). Via its IgM and IgG receptors, the B cell receives activation signals to process the antigen and subsequently migrate to the T-B border of the lymph node (11; 22; 23; 24).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, in the lymph node, naive B cells can interact with either macrophages or dendritic cells that carry SARS-CoV-2 antigens (N and S proteins) on their surface (20; 21). Via its IgM and IgG receptors, the B cell receives activation signals to process the antigen and subsequently migrate to the T-B border of the lymph node (11; 22; 23; 24).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly in contrast with other studies it was found that a 32 amino acid peptide (V551-L582) in the currently mapped RBD domain could be an immunodominant B Cell epitope equating to 58.7% of IgG samples tested [119][101] (See table 2). As above, naïve B cells expressing IgD + CD19 + CD27 -(see table 3) can be sole predictors of antibody titrations compared to control groups with high significance (P=0.009) [120]. Nonetheless, chronic COVID-19 disease patients presenting with DN (IgD -CD27 − ) B cells are shown to experience worse disease severity and complications.…”
Section: Isotypementioning
confidence: 86%
“…Interestingly in contrast with other studies it was found that a 32 amino acid peptide (V551-L582) in the currently mapped RBD domain could be an immunodominant B Cell epitope equating to 58.7% of IgG samples tested [116][101] (See table 2). As above, naïve B cells expressing IgD + CD19 + CD27 -(see table 3) can be sole predictors of antibody titrations compared to control groups with high significance (P=0.009) [117]. Nonetheless, chronic COVID-19 disease patients presenting with DN (IgD -CD27 − ) B cells are shown to experience worse disease severity and complications.…”
Section: Figure 3: Icos-icosl Pathway In T-helper Cells Iii) Role Of ...mentioning
confidence: 86%
“…High IgA to low IgG titrations cause pathological consequences in the host involving decreased pathogenic phagocytosis, increased cellular apoptosis, and increased NETosis as reported in late stage fatal COVID-19 cases. Patients possessing a high IgG to IgA ratio experience greater inflammatory dampening, and immune responses, resulting in better prognoses and early-latestage disease resolution [117]. Limited data exists to reveal why SARS-CoV-2 induced COVID-19 disease exhibits such a novel antibody profile regarding IgG1/IgA1 responses.…”
Section: Figure 3: Icos-icosl Pathway In T-helper Cells Iii) Role Of ...mentioning
confidence: 99%